Sovereign Wealth Funds and Long-Term Investments in Sub-Saharan Africa - Diallo, Boubacar; Tchana Tchana, Fulbert; Zeufack, Albert G. (World Bank, Washington, DC, 2017)
This paper explores the landscape, contributions, and determinants of sovereign wealth funds' long-term investments in Sub-Saharan Africa. The study finds that of all regions, Africa receives the lowest share of investment from sovereign wealth funds, and the landscape is dominated by Asian funds. The investment strategies of sovereign wealth funds established by African countries tend to be to invest less domestically and more abroad, contrary to Asian funds. In addition, using an enriched simple mean-variance portfolio model with an exponential utility function, the analysis shows that the investment rate of return and political connections have a positive and significant effect on sovereign wealth fund investments, and risk exerts a negative but not significant effect. The paper confirms these results empirically, using a database that includes 26 sovereign wealth fund investments over 1985-2013. Hence, sovereign wealth funds investing in Africa care more about high returns and the political interests of their country of origin than the risk of their investment.